(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research aims to analyze the influence of Nearpod interactive media based on the Deep Learning approach on the scientific literacy of fourth grade students at Cigugur State Elementary School on the subject of Climate and Change. The research uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research subjects consisted of 34 students who were divided into experimental class and control class, 17 students each. Data was collected through scientific literacy tests in the form of validated pre-tests and post-tests, then analyzed using the normality test, homogeneity test, Independent Samples t-Test, and N-Gain. The results showed that the post-test average for the experimental class reached 87.06, an increase of 18.24 points, while the control class reached 68.82 with an increase of 12.35 points. The Independent Samples t-Test results show a Sig value. (2-tailed) of 0.000 < 0.05. The N-Gain value for the experimental class is 0.6905, which is in the medium category. These results show that the use of Nearpod interactive media based on the Deep Learning approach has a significant effect on increasing students’ scientific literacy.